New Perspectives in Theology of Judaism - Spero, Shubert; Spero, Shubert (Academic Studies Press, 2021)
If it can be said that theology is the philosophical examination of a religion by an insider, then the present collection of essays by Shubert Spero offers us the proper formula for a truly authentic work. The author sets out to rigorously yet sensitively investigate some of the basic concepts and principles of classical Judaism. The topics addressed range from the familiar$1 (3z(BIs God Knowable?(3y (Band (3z(BJustifying Religious Belief(3y$1 (Bto the unusual$1 (B"Judaism and the Aesthetic,(3y z(BDoes Judaism Have a Theory of Self?(3y (Band (3z(BDoes Messianism Imply Inevitability?(3y (BCurrent issues are not neglected, and are addressed in sections such as (3z(BReligious Zionism: What is it?(3y (Band (3z(BThe Ethical Theory of Judaism.(3y (BWhile critical and analytic throughout, the author$1 (Bs style is clear and uncluttered and uses arguments to convince rather than to impress. Neither apologetic nor unnecessarily provocative, Shubert Spero provides a fresh approach to the neglected yet vital domain of Jewish theology.s
Knowledge Unlatched
English
Keywords: Philosophy of religion; Judaism; Religion; Philosophy; Religion; Judaism; Theology